Frontier-market economies as a new group of the financial periphery: patterns and transmission channels of global shocks - Daniela Prates; Barbara Fritz; Luiz Fernando de Paula (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2023)
This paper seeks to fill a gap in the literature on frontier market economies (FMEs) with the following two research questions: (i) Which are the drivers of FMEs' integration into financial globalisation? (ii) What explains the greater vulnerability of FMEs compared to emerging market economies (EMEs) to global financial shocks? We argue that the emergence of FMEs as a new group of the financial periphery fills a vacuum left for global investors by the major EMEs, whose spreads declined in the past decade due to high foreign currency reserve accumulation and other EME-related factors. To answer the second question, we introduce the concept of financial hierarchy as a second layer of the currency hierarchy: while the currency hierarchy is organized by the different degrees of liquidity premia currencies offer, in the financial hierarchy, not currencies, but financial assets are placed according to the nominal yield. While FMEs' currencies have a lower liquidity premium than those of EMEs, the difference between them is not vast – as both are not accepted at the international level – and are insufficient to explain FMEs' greater vulnerability to external financial shocks. We argue in the paper that this vulnerability stems mainly from the position of FMEs' at the bottom of the financial hierarchy, which results in a different pattern of international financial integration.
Keywords: E6; F3; F6; 330; frontier market economies; financial periphery; financial globalisation; patterns of international financial integration